2000
DOI: 10.1074/jbc.m005338200
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of GIRK1 at Asn119 and ROMK1 at Asn117 Has Different Consequences in Potassium Channel Function

Abstract: GIRK (G protein-gated inward rectifier K؉ channel) proteins play critical functional roles in heart and brain physiology. Using antibodies directed to either GIRK1 or GIRK4, site-directed mutagenesis, and specific glycosidases, we have investigated the effects of glycosylation in the biosynthesis and heteromerization of these proteins expressed in oocytes. Both GIRK1 and GIRK4 have one extracellular consensus N-glycosylation site. Using chimeras between GIRK1 and GIRK4 as well as a GIRK1 N-glycosylation mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…N-linked glycosylation has also been reported to be required for the cell surface expression of ligand-gated channels including nicotinic acetylcholine receptor (16) and ATP purinergic receptors P2X1 and P2X2 (24 33). In contrast, other studies have shown that N-linked glycosylation is not required for the cell surface expression of cystic fibrosis transmembrane conductance regulator (17), cyclic nucleotide-gated channels (25), inward rectifier K ϩ channel GIRK1 (19), and voltagegated K ϩ channels such as Kv1.1 and Shaker (5,28). Previous biochemical studies of HERG channels in transfected cells and native cardiac tissues have shown that HERG channel protein is modified by N-linked glycosylation (7,20,21,37,38).…”
Section: Discussionmentioning
confidence: 69%
“…N-linked glycosylation has also been reported to be required for the cell surface expression of ligand-gated channels including nicotinic acetylcholine receptor (16) and ATP purinergic receptors P2X1 and P2X2 (24 33). In contrast, other studies have shown that N-linked glycosylation is not required for the cell surface expression of cystic fibrosis transmembrane conductance regulator (17), cyclic nucleotide-gated channels (25), inward rectifier K ϩ channel GIRK1 (19), and voltagegated K ϩ channels such as Kv1.1 and Shaker (5,28). Previous biochemical studies of HERG channels in transfected cells and native cardiac tissues have shown that HERG channel protein is modified by N-linked glycosylation (7,20,21,37,38).…”
Section: Discussionmentioning
confidence: 69%
“…For example, changes in glycosylation or sialylation altered the gating of potassium channels such as K v LQT1/mink, ROMK1, K v 1.1, and K v 4.3 [10,32,41,44]. Whereas other potassium channels such as squid K v 1 type and G-protein-coupled inward rectifying potassium channels appear to be unaffected by changes in glycosylation/sialylation [22,26]. These data suggest possible isoform specific differences in the sensitivity of K + channels to glycosylation.…”
Section: Introductionmentioning
confidence: 75%
“…However, the exact role may vary among different channels. For example, glycosylation reflects surface expression of HERG (23,30), alters the voltage dependence of activation of Kv1.1 and KvLQT1/minK, and modulates the open probability of ROMK1 (20,31). We and other investigators have shown that N-linked glycosylation is not essential for surface expression of Kv1.1 and Shaker channels in Xenopus oocytes (1).…”
Section: Discussionmentioning
confidence: 95%